Fibrewise soft bitopological spaces. Issue 7 (3rd October 2021) - Yousif, Y. Y.; Hussain, L. A.; Hussain, M. A.
Abstract: We introduce and discussarecent type of fibrewise topological spaces, namely fibrewise soft bitopological spaces. Also, we introduce the concepts of fibrewise closed soft bitopological spaces, fibrewise open soft bitopological spaces, fibrewise locally sliceable soft bitopological spaces and fibrewise locally sectionable soft bitopological spaces. Furthermore, we state and prove several propositions concerning these concepts.